Airline seat management with round-trip requests - You, P.-S. (Yugoslav Journal of Operations Research; Vol 14 No 2 (2004): Vol. 14 No. 2, 2016)
Consider a multi-period multi-fare class airline booking problem related to a two-leg airline network. Travel requests include outbound, inbound trip, and round trips. The round-trip refers to a journey comprising both outbound and inbound trips. To develop a dynamic-nested booking decision-making system for the airline network, this study designs a dynamic model that enables the airline reservations system to devise a set of dynamic decision rules for any given booking status. The booking process is found to be controlled by some set of booking thresholds.